Sentencing Eddie - Lynch, Gerard E. (2001)
The mandatory minimum sentences attached to federal narcotics violations have come in for plenty of criticism. The United States Sentencing Commission in 1991 submitted a lengthy report critical of the mandatory minimum provisions. A political protest organization, Families Against Mandatory Minimums, has been formed, and has gotten some media attention. Newspaper columnists,professional commentators, judges, and academics, have criticized the statutes. Amidst the controversy over President Clinton's last-minute pardons of various offenders, his pardons of a number of marginal defendants sentenced to lengthy terms under these statutes have drawn little or no objection. Even Chief Justice Rehnquist, a strong voice for law enforcement, has denounced mandatory minimum sentences as having little serious justification